The Impact of Inflation, Exchange Rate, Trade and Foreign Direct Investment on Economic Growth Of The Gambia: Evidence From ARDL Approach - Minteh, Salim; Amadou Gisseh; Khan, Ebrima (Indonesian Journal Publisher, 2025)
The study investigates the relationship between Foreign Direct Investment (FDI), trade flows, inflation rates, and exchange rates in relation to economic growth in The Gambia during the period from 1970 to 2023. The investigation aims to examine both long-term and short-term macroeconomic interrelations between these variables to determine their effects on GDP. The research employs the Auto Regressive Distributed Lag (ARDL) methodology to demonstrate a sustainable long-term relationship between trade, inflation, FDI, and exchange rates with GDP. The statistical analysis reveals a dual effect: inflation and trade lead to GDP increases, while FDI and exchange rates result in GDP decreases. The investigation finds no significant causal relationships between the variables to predict future trends based on past observations. The study faces limitations due to reliance on limited data sources and its focus mainly on The Gambia, making generalization to other contexts challenging. The Gambia presents an economic system that requires official policies to support trade activities and control inflation while addressing the negative effects of FDI on domestic business investments. This research study provides significant economic insights into The Gambia and its important macroeconomic relationships.